Ivermectin-induced bacterial gut dysbiosis does not increase susceptibility to Pseudomonas aeruginosa lung infection - Belo, Thiago Caetano Andrade (2022)
The maintenance of gut microbiota is essential for a physiological, metabolic, immune balance and to influence the health-disease state. Some studies have suggested the use of ivermectin for Covid-19 treatment and even though it was later refuted by studies and rejected by drug control agencies around the world, its use remained and was encouraged by various segments of government and health. The objective of this work was to evaluate the influence of oral ivermectin use on the bacterial gut microbiota and what are the effects of this gut dysbiosis in Pseudomonas aeruginosa opportunistic pneumonia in mice. For this, C57BL/6 isogenic mice were treated for 7 consecutive days with PBS or ivermectin by gavage. There were no significant differences in the mice’s weight and the feed consumed during the experimental period. However, there was an increase in feces moisture and uneven consistency in the ivermectin- treated group. Through metagenomic analysis of the feces’ total DNA, it was observed a decrease in the phyla Bacteroidetes, Firmicutes, Proteobacteria, and Tenericutes and an increase in the phylum Verrucomicrobia in mice ivermectin treated, compared to the PBS group. Furthermore, the cecal content of ivermectin-treated mice showed to be more immunostimulatory in macrophages derived from murine bone marrow due to the increase in CD86 molecules labeling in the membrane of these cells when analyzed by immunofluorescence, in addition to the increase in IL-6 secretion and decrease in IL-10, quantified by ELISA. The cecal tissue organization of ivermectin-treated mice was altered, in addition to the ivermectin treatment induced liver tissue damage and increased the expression of pro and anti-inflammatory cytokines in the liver. When mice were infected with P. aeruginosa, there was no increased susceptibility to infection in gut-dysbiotic mice, showing similarity between the PBS-treated and ivermectin-treated groups and infected in the viable recovery bacteria in the lung, liver, spleen, and kidney, histopathological analysis and expression of cytokines in the lung or secretion of pro- or anti-inflammatory cytokines from cultivated splenocytes from animals infected and restimulated with P. aeruginosa. Therefore, an extension in liver damage and up-regulation in the expression of pro-and anti-inflammatory cytokines were observed treated with ivermectin-treated and infected with P. aeruginosa group. It is possible to conclude that the ivermectin’s continuous usage did not lead to a greater susceptibility or resistance to P. aeruginosa, despite the effect of this drug on the gut microbiota of mice-treated.